OPTIMALISASI BADAN USAHA MILIK DESA (BUMDES) MELALUI PENGELOLAAN PRODUKSI IKAN BANDENG DI DESA KALANGANYAR KECAMATAN SEDATI KABUPATEN SIDOARJO - Arneta Dia Novitasari; Heru Irianto; Tri Prasetijowati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2022)
Village Owned Enterprises are business entities that are established and owned by the village, one of which aims to increase the village's potential progress and also the village's original income. However, it is often found that these objectives have not been met because the income and contributions are not significant. Therefore it is necessary to optimize the management of BUMDes in increasing the management of milkfish productivity in Kalanganyar Village. Kalanganyar Village is one of the villages that produces the largest milkfish production in Sidoarjo Regency, it is necessary to have Optimal management so that in addition to increasing the potential of the Village it will also make this Sidoarjo icon more prominent. Researchers used descriptive qualitative methods, data collection techniques through interviews, observation and documentation. The aim of the research is to analyze the optimization of BUMDes through the management of milkfish productivity. The results of the study show that the management of BUMDes has been going well and has had a positive impact on the community but is still not optimal, because several indicators have not been fulfilled (1) infrastructure that is still not optimal and inadequate, (2) human resources, (3) adequate capital owned by BUMDes is still lacking in managing village potential and planning optimal activities